Electrolytic capacitor and method for manufacturing electrolytic capacitor
By placing a layer containing conductive polymers and insulating substances between the anode foil and the cathode foil of the electrolytic capacitor, the problems of short circuit, increase leakage current and decrease in the withstand voltage caused by no spacer in the prior art are solved, and an electrolytic capacitor with high reliability and high volume capacity density is achieved.
Patent Information
- Application Number
- CN202380056359.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-29
- Filing Date
- 2023-07-27
- Publication Date
- 2025-02-28
AI Technical Summary
In the absence of spacers, existing electrolytic capacitors are prone to short circuits, increased leakage current and reduced withstand voltage, and at the same time, the volume capacity density is low.
By placing a layer containing conductive polymers and insulating substances between the anode foil and the cathode foil, a dielectric layer is formed to ensure the distance between the anode foil and the cathode foil, avoid short circuits and performance degradation, and at the same time, no spacers are used to improve the volume capacity density.
Even without spacers, the electrolytic capacitor has high reliability and improved volume capacity density, and the problems of short circuit and performance are avoided.
Smart Images

Figure CN119547168A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to an electrolytic capacitor and a method for manufacturing an electrolytic capacitor. Background Art
[0002] As an electrolytic capacitor, there is known an electrolytic capacitor including a winding body of an anode foil, a separator, and a cathode foil. One example of such an electrolytic capacitor includes a conductive polymer layer disposed in the winding body. The conductive polymer layer is formed, for example, by impregnating the winding body with a dispersion containing a conductive polymer. Various schemes have been proposed in the past regarding an electrolytic capacitor including a conductive polymer layer and a method for manufacturing the same.
[0003] Patent document 1 (Japanese Patent No. 5062738) discloses "a conductive composition comprising a conductive polymer synthesized by oxidative polymerization of pyrrole or a derivative thereof using an organic sulfonate and a persulfate, wherein the organic sulfonate is an organic sulfonate comprising a polystyrene sulfonate having a number average molecular weight of 10,000 to 300,000 and an aromatic sulfonate, wherein the aromatic sulfonic acid portion of the aromatic sulfonate accounts for 20% to 50% by mass relative to the polystyrene sulfonic acid portion of the polystyrene sulfonate, and the pH of the dispersion having a total concentration of 1% by mass of the conductive polymer and a substance derived from an added pH-increasing agent is 1.5 to 4.5."
[0004] Patent document 2 (Japanese Patent Publication No. 2007-27767) discloses a method comprising: a step of applying a dispersion a) containing at least particles b of a predetermined conductive polymer, a binder c) and a dispersant d) to a capacitor body containing at least a solid electrolyte, and a step of removing at least a portion of the dispersant d) and / or curing the binder c) in order to form an outer layer of the conductive polymer.
[0005] Patent document 3 (Japanese Patent Gazette No. 6951159) discloses "a capacitor comprising an anode including a valve metal, a dielectric layer including an oxide of the valve metal, a cathode made of a conductive material provided on the side of the dielectric layer opposite to the anode, and a solid electrolyte layer formed between the dielectric layer and the cathode, the solid electrolyte layer having a conductive composite including a π-conjugated conductive polymer and a polyanion and a binder, the binder containing a styrene-butadiene rubber."
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent No. 5062738
[0009] Patent Document 2: Japanese Patent Application Publication No. 2007-27767
[0010] Patent Document 3: Japanese Patent No. 6951159 Summary of the invention
[0011] Problems to be solved by the invention
[0012] By using a spacer, it is possible to prevent the distance between the anode foil and the cathode foil from being too short. Therefore, by using a spacer, it is possible to prevent short circuits, increases in leakage current, decreases in withstand voltage, etc. On the other hand, due to the presence of the spacer, the volume capacity density (capacity density per unit volume) is reduced.
[0013] Under such circumstances, one of the objects of the present application is to provide an electrolytic capacitor having high reliability even without a spacer and a method for manufacturing the same.
[0014] Means for solving problems
[0015] One aspect of the present application relates to an electrolytic capacitor, which includes a laminate of an anode foil and a cathode foil having a dielectric layer formed on the surface, and a layer containing a conductive polymer and an insulating material disposed between the dielectric layer and the cathode foil, wherein the insulating material is at least one selected from insulating fibers and insulating particles, and no spacer is disposed between the anode foil and the cathode foil.
[0016] Another aspect of the present application relates to a method for manufacturing an electrolytic capacitor including an anode foil and a cathode foil having a dielectric layer formed on the surface. The manufacturing method sequentially comprises: step (i), applying a dispersion containing a conductive polymer and an insulating substance to at least one element selected from the above-mentioned dielectric layer and the above-mentioned cathode foil and drying it, thereby forming a layer containing the above-mentioned conductive polymer and the above-mentioned insulating substance on the above-mentioned at least one element; and step (ii), stacking the above-mentioned anode foil and the above-mentioned cathode foil in a manner such that the above-mentioned layer is arranged between the above-mentioned dielectric layer and the above-mentioned cathode foil to form a stacked body, the above-mentioned insulating substance includes at least one selected from insulating fibers and insulating particles, and in the above-mentioned step (ii), the above-mentioned anode foil and the above-mentioned cathode foil are stacked without a spacer.
[0017] Effects of the Invention
[0018] According to the present application, a highly reliable electrolytic capacitor can be obtained even without a spacer, and the volume capacity density of the electrolytic capacitor can be increased.
[0019] The novel features of the present invention are described in the scope of the appended claims, but the present invention in both structure and content together with other objects and features of the present invention should be more fully understood through the following detailed description with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 It is a side view schematically showing an electrolytic capacitor according to an embodiment of the present application.
[0021] Figure 2 It is an exploded perspective view schematically showing a capacitor element according to an embodiment of the present application.
[0022] Figure 3A This is a cross-sectional view schematically showing a part of an example of an anode foil having a layer containing a conductive polymer formed thereon.
[0023] Figure 3B This is a cross-sectional view schematically showing a part of another example of the anode foil having a layer containing a conductive polymer formed thereon. DETAILED DESCRIPTION
[0024] Hereinafter, the embodiments of the present application will be described with examples, but the present application is not limited to the examples described below. In the following description, specific numerical values and materials are sometimes exemplified, but as long as the effect of the present application can be obtained, other numerical values and other materials may also be applied. In this specification, the description of "numerical value A to numerical value B" includes numerical value A and numerical value B, and may be renamed as "numerical value A or more and numerical value B or less". In the following description, when the lower limit and upper limit of numerical values for specific physical properties, conditions, etc. are exemplified, as long as the lower limit is not above the upper limit, any one of the exemplified lower limits may be arbitrarily combined with any one of the exemplified upper limits. In the following description, when the examples of constituent elements are listed, as long as there is no special record, only one of the listed examples may be used, or a plurality of the listed examples may be used in combination.
[0025] (Method for manufacturing electrolytic capacitor)
[0026] The manufacturing method of the present embodiment is a manufacturing method of an electrolytic capacitor including an anode foil and a cathode foil having a dielectric layer formed on the surface. Hereinafter, the manufacturing method is sometimes referred to as "manufacturing method (M)". The manufacturing method (M) includes steps (i) and (ii) in sequence. These steps are described as follows.
[0027] (Process (i))
[0028] Step (i) is a step of applying a dispersion containing a conductive polymer and an insulating substance to at least one element selected from the dielectric layer formed on the surface of the anode foil and the cathode foil and drying the dispersion, thereby forming a layer containing a conductive polymer and an insulating substance on the at least one element. Hereinafter, the insulating substance, the dispersion, and the layer may be referred to as "insulating substance (I)", "dispersion (D1)", and "layer (PL)", respectively.
[0029] The dispersion (D1) contains an insulating substance (I). Therefore, by forming the layer (PL) using the dispersion (D1), the insulating substance (I) can be used to ensure the spacing between the anode foil and the cathode foil when forming the laminate. Therefore, by using the dispersion (D1), a highly reliable electrolytic capacitor can be obtained even without a spacer. By not using a spacer, the ESR of the electrolytic capacitor can be reduced. In addition, by not using a spacer, the volume capacity density of the electrolytic capacitor can be increased.
[0030] The coating method and drying method of the dispersion (D1) are not particularly limited, and known methods can be used. The coating method can be a method using a coating machine or a method of spraying the dispersion (D1). Alternatively, at least one of the above elements can be immersed in the dispersion (D1). The drying of the dispersion (D1) can be carried out by removing at least a portion of the dispersion medium by heating. For example, the heating can be carried out at a temperature above 100°C (for example, above 120°C, above 140°C). There is no upper limit to the heating temperature, but it is carried out at a temperature that does not affect components such as conductive polymers, for example, at a temperature below 160°C. The heating time is not limited, as long as the heating time is determined by considering the evaporation amount of the dispersion medium. Drying can also be carried out under reduced pressure. These coating methods and drying methods can also be applied to the coating and drying described below.
[0031] The at least one element may be a dielectric layer, a cathode foil, or a dielectric layer and a cathode foil. The at least one element preferably includes a dielectric layer. By forming a layer (PL) on the dielectric layer, an insulating material (I) can be arranged on the defective portion of the dielectric layer. Thus, it is possible to suppress the performance degradation (increase in leakage current, decrease in withstand voltage, etc.) caused by the adhesion of the conductive polymer to the defective portion of the dielectric layer on the surface of the anode foil.
[0032] From one viewpoint, the layer (PL) is a conductive polymer layer containing a conductive polymer. The layer (PL), or the layer (PL) and the liquid component (L) described below, can function as an electrolyte.
[0033] The thickness T of the conductive polymer layer (including layer (PL)) disposed between the anode foil and the cathode foil is preferably 10 μm or more, 30 μm or more, or 50 μm or more. By setting the thickness T to 30 μm or more, the spacing between the anode foil and the cathode foil can be ensured. There is no particular upper limit to the thickness T, but an excessively thick conductive polymer layer will reduce the effect of not using a spacer, and increase the formation time and formation cost. Therefore, the thickness T may be 80 μm or less, or 60 μm or less.
[0034] When the conductive polymer layer disposed between the anode foil and the cathode foil is formed only of the layer (PL), the thickness of the layer (PL) may be within the range exemplified for the thickness T. When the conductive polymer layer disposed between the anode foil and the cathode foil is formed of the layer (PL) and another conductive polymer layer (e.g., the second conductive polymer layer described later), the thickness of the layer (PL) may be within a range smaller than the range exemplified for the thickness T.
[0035] (Insulating material (I))
[0036] The insulating material (I) includes at least one selected from insulating fibers and insulating particles. The insulating material (I) may consist of only insulating fibers, only insulating particles, or both. From the perspective of being easy to uniformly adhere to the dielectric layer, the insulating material (I) preferably includes insulating fibers. By including the insulating material (I), even when a spacer is not used in the electrolytic capacitor, a decrease in withstand voltage and an increase in leakage current can be suppressed.
[0037] The insulating fiber used as the insulating material (I) may include a fiber containing at least one substance selected from cellulose, rayon, aramid, polyester, polyimide, and nylon, or may be a fiber formed from the at least one substance. By using these insulating fibers, the dispersibility in the dispersion (D1) can be improved, and in particular, the reduction in the withstand voltage of the electrolytic capacitor can be suppressed. Alternatively, insulating fibers other than these may be used.
[0038] The average diameter of the insulating fiber can be greater than 0.1 μm, greater than 1 μm, or greater than 10 μm, and can be less than 100 μm, or less than 50 μm. It should be noted that the cross-section of the insulating fiber can be roughly a perfect circle, or it can be a shape other than a perfect circle (for example, an ellipse). The so-called fiber diameter refers to the equivalent circle diameter. By setting the average diameter of the insulating fiber to a range of 1 μm to 50 μm (for example, a range of 10 μm to 50 μm), the effect of the present application can be improved. The average diameter of the fiber can be obtained by measuring the diameter (equivalent circle diameter) of any position of 30 randomly selected fibers and arithmetically averaging the 30 measured diameters. The equivalent circle diameter can be measured, for example, by analyzing an image of a cross section of the fiber.
[0039] The average fiber length of the insulating fiber may be 100 μm or more. The upper limit of the average fiber length is not particularly limited, and may be, for example, 5000 μm or less. The average fiber length can be obtained by taking the arithmetic mean of the lengths of 30 fibers.
[0040] The insulating particles used as the insulating material (I) may include particles containing at least one substance selected from polyolefin, polyester, polytetrafluoroethylene and ceramic (insulating ceramic) from the viewpoint of suppressing the reduction of the withstand voltage of the electrolytic capacitor, or may be particles formed of the at least one substance. Alternatively, insulating particles other than these may be used.
[0041] The average particle size of the insulating particles may be 0.1 μm or more, 10 μm or more, or 20 μm or more, and may be 100 μm or less, or 50 μm or less. In this specification, the average particle size is the median diameter (D50) at which the cumulative volume reaches 50% in the volume-based particle size distribution. The median diameter can be obtained using a laser diffraction / scattering particle size distribution measuring device.
[0042] The shape of the insulating particles is not particularly limited, and may be spherical (including ellipsoidal, etc.), scaly, needle-like, or lattice-like. Alternatively, the shape of the insulating particles may not be particularly specified.
[0043] Insulating fibers and insulating particles are sold in various materials and shapes. As the insulating material (I), commercially available insulating fibers and / or insulating particles may be used. Alternatively, insulating fibers and / or insulating particles produced by known methods may be used.
[0044] The content Ci (mass %) of the insulating substance (I) in the dispersion (D1) may be 0.1 mass % or more, or 1.0 mass % or more, and may be 5.0 mass % or less, or 3.0 mass % or less. By setting the content to 1.0 mass % or more, the effect of the present application can be improved. By setting the content to 3.0 mass % or less, the decrease in the conductivity of the conductive polymer layer can be suppressed.
[0045] The ratio Ci / Cc of the content Ci (mass %) to the content Cc (mass %) of the conductive polymer in the dispersion (D1) may be 0.1 or more, or 0.5 or more, and may be 2.0 or less, or 1.0 or less. By setting the ratio Ci / Cc to 0.5 or more, the effect of the present application can be improved. By setting the ratio Ci / Cc to 1.0 or less, the decrease in the conductivity of the conductive polymer layer can be suppressed.
[0046] (Dispersion medium)
[0047] The dispersion medium is a medium for dispersing the conductive polymer. The dispersion medium preferably contains water. The content of water in the dispersion medium may be 50% by mass or more, 70% by mass or more, 90% by mass or more, or 95% by mass or more. The content may also be 100% by mass. That is, the dispersion medium may be water. The dispersion medium may also contain an organic solvent other than water. It should be noted that the additive (A) is not included in the dispersion medium.
[0048] (Conductive polymer)
[0049] The conductive polymer is not particularly limited as long as it can be used in an electrolytic capacitor. As the conductive polymer, a known conductive polymer used as an electrolyte for an electrolytic capacitor can be used.
[0050] Examples of conductive polymers include polypyrrole, polythiophene, polyfuran, polyaniline, polyacetylene and their derivatives. The derivatives include polymers with polypyrrole, polythiophene, polyfuran, polyaniline and polyacetylene as basic skeletons. For example, poly(3,4-ethylenedioxythiophene) is included in the derivatives of polythiophene. These conductive polymers can be used alone or in combination. In addition, the conductive polymer can be a copolymer of two or more monomers. The weight average molecular weight of the conductive polymer is not particularly limited, for example, it can be in the range of 1000 to 100000. A preferred example of a conductive polymer is poly(3,4-ethylenedioxythiophene) (PEDOT).
[0051] The conductive polymer may be doped with a dopant. From the viewpoint of suppressing dedoping from the conductive polymer, it is preferred to use a polymer dopant as the dopant. Examples of polymer dopants include polyvinyl sulfonic acid, polystyrene sulfonic acid, polyallyl sulfonic acid, polyacrylic acid sulfonic acid, polymethacrylic acid sulfonic acid, poly (2-acrylamide-2-methylpropane sulfonic acid), polyisoprene sulfonic acid, polyacrylic acid, etc. They can be used alone or in combination of two or more. At least a portion of them can be added in the form of a salt. A preferred example of a dopant is polystyrene sulfonic acid (PSS). In a preferred example, the conductive polymer is poly (3,4-ethylenedioxythiophene) and the dopant is polystyrene sulfonic acid.
[0052] The dopant may be a dopant containing an acidic group or a polymer dopant containing an acidic group. Examples of acidic groups include sulfonic acid groups, carboxyl groups, etc. The polymer dopant containing an acidic group is a polymer (polymer) in which at least a portion of the structural unit contains an acidic group. Examples of such a polymer dopant include the above-mentioned polymer dopant.
[0053] The weight average molecular weight of the dopant is not particularly limited, but from the viewpoint of facilitating the formation of a uniform conductive polymer layer, the weight average molecular weight of the dopant can be in the range of 1,000 to 100,000.
[0054] When a conductive polymer doped with a dopant is used, the pH of the dispersion (D1) is preferably less than 7.0, and may be 6.0 or less or 5.0 or less in order to suppress dedoping of the dopant. The pH of the dispersion (D1) may be 1.0 or more, 2.0 or more, or 3.0 or more.
[0055] The conductive polymer may be present in the dispersion (D1) in the form of particles. The average particle size (D50) of the conductive polymer particles may be 10 μm or more, or 20 μm or more, and 100 μm or less.
[0056] The content of the conductive polymer in the dispersion (D1) may be 0.5% by mass or more, or 1.0% by mass or more, and may be 4.0% by mass or less, 3.0% by mass or less, or 2.0% by mass or less. The content may be in the range of 0.5 to 4.0% by mass, or in the range of 1.0 to 4.0% by mass. In any of these ranges, the upper limit may be 3.0% by mass or 2.0% by mass. In terms of the excellent physical properties of the dispersion (D1) and its stability over time, and the excellent balance between the ESR and cost of the electrolytic capacitor, the content is preferably in the range of 1.0 to 5.0% by mass (e.g., 1.0 to 3.0% by mass).
[0057] The mass of the dopant contained in the dispersion (D1) is not particularly limited, and may be in the range of 0.1 to 5 times (eg, 0.5 to 3 times) the mass of the conductive polymer contained in the dispersion (D1).
[0058] The method for producing the dispersion (D1) is not particularly limited. For example, the dispersion (D1) can be produced by dispersing and dissolving the components of the dispersion (D1) in a dispersion medium. Specifically, the dispersion (D1) can be produced by adding the components of the dispersion (D1) to a dispersion medium and stirring.
[0059] (additive)
[0060] The dispersion (D1) may contain an additive containing a hydroxyl group and water as a dispersion medium. Hereinafter, the additive may be sometimes referred to as "additive (A)". The ratio Mh / Mt of the total formula weight Mh of the hydroxyl groups contained in the additive (A) to the molecular weight Mt of the additive may be 0.001 or more. In the case of ethylene glycol (HO-CH2-CH2-OH), the molecular weight Mt is 62, and the total formula weight Mh of the two hydroxyl groups is 34. Therefore, Mh / Mt=34 / 62=0.55. In the case where the molecular weight of the additive (A) is not constant, the molecular weight of the additive (A) may use the weight average molecular weight.
[0061] Conductive polymers (e.g., conductive polymer particles) and insulating substances (I) are prone to agglomeration. By adding the additive (A), agglomeration of the two can be suppressed. Therefore, by forming a conductive polymer layer using a dispersion (D1) to which the additive (A) is added, a conductive polymer layer with high dispersibility of the insulating substance (I) can be formed.
[0062] The ratio Mh / Mt may be 0.03 or more, or 0.07 or more, and may be 0.9 or less. By setting the ratio Mh / Mt to 0.03 or more, the effect of the additive (A) can be sufficiently obtained.
[0063] The molecular weight of the additive (A) is preferably 500 or less. By setting the molecular weight to 500 or less, the dispersibility in the dispersion (D1) can be improved. As a result, the additive (A) is easily attached to the defective portion of the dielectric layer. There is no particular limitation on the lower limit of the molecular weight, but it may be 44 or more, 80 or more, or 150 or more. The molecular weight may be 500 or less, 400 or less, 200 or less, or 120 or less.
[0064] The number of hydroxyl groups contained in the additive (A) is 1 or more or 2 or more, and may be 6 or less or 3 or less. From the viewpoint of the repairability of the defective portion of the dielectric layer, the number of hydroxyl groups is preferably 3 or less.
[0065] Examples of additives (A) include polyols. In this specification, polyols refer to organic compounds containing two or more hydroxyl groups. Examples of polyols include glycols, glycerols, and sugar alcohols. Polyols can be hydrocarbon compounds substituted with two or more hydroxyl groups (e.g., aliphatic hydrocarbons substituted with two or more hydroxyl groups). Additive (A) is preferably a compound soluble in water. Additive (A) can also be an organic compound having three or less hydroxyl groups (e.g., a trivalent or less lower alcohol). The molecular weight of the organic compound can be 500 or less.
[0066] Examples of glycols include alkylene glycols (ethylene glycol, propylene glycol, etc.), diethylene glycol, triethylene glycol, polyalkylene glycols (e.g., polyethylene glycol), polyoxyethylene polyoxypropylene glycol (ethylene oxide-propylene oxide copolymer), etc. Examples of glycerols include glycerol and polyglycerol, etc. Examples of sugar alcohols include mannitol, xylitol, sorbitol, erythritol, and pentaerythritol, etc.
[0067] The additive (A) may be at least one selected from glycols, glycerols and sugar alcohols. For example, the additive (A) may be at least one selected from ethylene glycol, polyethylene glycol, diethylene glycol, triethylene glycol, glycerol, polyglycerol, erythritol, xylitol, sorbitol and mannitol. A preferred example of the additive (A) is ethylene glycol.
[0068] The ratio Ca / Ci of the content Ca (mass %) of the additive (A) in the dispersion (D1) to the content Ci (mass %) of the insulating substance (I) in the dispersion (D1) may be 0.1 or more, or 1.0 or more, and 8.0 or less, or 4.0 or less.
[0069] The manufacturing method (M) may include a step of forming a conductive polymer layer using a dispersion (D2). The dispersion (D2) is a dispersion obtained by removing an insulating substance (I) from a dispersion exemplified as the dispersion (D1). For example, after forming a first conductive polymer layer (layer (PL1)) using the dispersion (D1), a second conductive polymer layer may be formed on the first conductive polymer layer using the dispersion (D2). It should be noted that in the above-mentioned steps, the step of applying the dispersion (dispersion (D1), dispersion (D2)) and drying may be performed only once or may be repeated multiple times. By repeating this step multiple times, the conductive polymer layer can be thickened.
[0070] (Step (ii))
[0071] Step (ii) is a step of forming a laminate by stacking the anode foil and the cathode foil in a manner that the layer (PL) is arranged between the dielectric layer formed on the surface of the anode foil and the cathode foil. In step (ii), the anode foil and the cathode foil are stacked without a separator. According to step (ii), a laminate (capacitor element) that does not include a separator arranged between the anode foil and the cathode foil can be formed. Therefore, an electrolytic capacitor with a high volume capacity density can be manufactured. Since the layer (PL) contains an insulating material (I), the distance between the electrodes of the anode foil and the cathode foil can be maintained. As a result, the performance degradation caused by the anode foil and the cathode foil being too close can be suppressed.
[0072] The manufacturing method can be used for a stacked electrolytic capacitor. The capacitor element of the stacked electrolytic capacitor includes a stack of at least one anode foil and at least one cathode foil. The stack can be a stack formed by stacking them in one direction. In this case, the electrolytic capacitor can include a plurality of capacitor elements.
[0073] The laminate may also be a wound body obtained by winding the anode foil and the cathode foil. That is, in step (ii), the anode foil and the cathode foil may be stacked by winding the anode foil and the cathode foil. In the wound body, the anode foil and the cathode foil are stacked in the radial direction. Therefore, the wound body is also a laminate.
[0074] The manufacturing method (M) may further include a step (Z) of impregnating the stack with a liquid component after step (ii). The liquid component is sometimes referred to as "liquid component (L)" hereinafter. The method of impregnating the stack with the liquid component (L) is not particularly limited. Step (Z) may also be performed by immersing the stack in the liquid component (L). Alternatively, step (Z) may also be performed by accommodating the liquid component (L) and the stack in an outer packaging body (shell). Examples of the liquid component (L) will be described later.
[0075] The manufacturing method (M) may include a step (Y1) and a step (Y2) after the step (ii) and before the step (Z). Hereinafter, the step (Y1) and the step (Y2) are sometimes collectively referred to as the "step (Y)". The step (Y1) is a step of impregnating the laminate with a treatment liquid containing an organic compound containing two or more hydroxyl groups and water. Hereinafter, the organic compound and the treatment liquid are sometimes referred to as the "organic compound (C)" and the "treatment liquid (S)". The step (Y2) is a step of evaporating at least a portion of the water in the treatment liquid (S).
[0076] By performing step (Y), the organic compound (C) can be disposed in the conductive polymer layer. This facilitates the liquid component (L) to be impregnated into the laminate in step (Z).
[0077] In step (Y1), the method of impregnating the laminate with the treatment liquid (S) is not limited. For example, the laminate may be immersed in the treatment liquid (S). In step (Y2), the step of evaporating at least a portion of the water in the treatment liquid (S) is not limited. Step (Y2) may be performed under the conditions exemplified for drying the dispersion (D1).
[0078] Examples of the organic compound (C) include polyols. Examples of the polyols include the compounds given as examples of the polyols of the additive (A).
[0079] The water content in the treatment liquid (S) may be 40% by mass or more, 60% by mass or more, 80% by mass or more, 90% by mass or more, or 95% by mass or more. The water content may be 99% by mass or less, 95% by mass or less, 90% by mass or less, or 80% by mass or less.
[0080] The content of the organic compound (C) in the treatment liquid (S) may be 1.0 mass % or more, 5.0 mass % or more, 10 mass % or more, or 20 mass % or more. The content may be 60 mass % or less, 40 mass % or less, 20 mass % or less, or 10 mass % or less.
[0081] The laminate (capacitor element) after step (ii) is sealed in an outer package. In this way, a laminated electrolytic capacitor can be manufactured. As described above, step (Z) can be performed after step (ii). Alternatively, step (Y) and step (Z) can be performed after step (ii).
[0082] The impregnation of the layered product with the liquid (dispersion (D1), dispersion (D2), treatment liquid (S), liquid component (L), etc.) can be performed by immersing the layered product in the liquid. The subsequent drying can be performed by heating the layered product. The heating can be performed under reduced pressure.
[0083] An example of the structure and components of the electrolytic capacitor manufactured by the manufacturing method (M) is described below. It should be noted that the structure and components of the electrolytic capacitor are not limited to the following example. Components other than the characteristic components in the present application can use known components of electrolytic capacitors.
[0084] The electrolytic capacitor includes a capacitor element. The capacitor element includes at least one anode foil, at least one cathode foil, and an electrolyte layer disposed between the anode foil and the cathode foil.
[0085] (Anode foil)
[0086] The anode foil may be a metal foil with a porous surface. The dielectric layer is formed on at least a portion of the surface of the anode foil. The thickness of the anode foil is not particularly limited, and may be in the range of 15 μm to 300 μm.
[0087] The material of the anode foil can be a valve metal, an alloy containing a valve metal, or a valve metal compound. Examples of valve metals include titanium (Ti), tantalum (Ta), niobium (Nb), aluminum (Al), etc. The anode foil can be formed by etching the surface of a metal foil (e.g., aluminum foil) that serves as a material. The dielectric layer formed on the surface of the anode foil can be formed by performing a chemical treatment on the surface of the metal foil. The method of the chemical treatment is not limited, and a known chemical treatment method can be applied.
[0088] (Cathode foil)
[0089] The cathode foil is not particularly limited as long as it has the function of serving as a cathode. Examples of cathode foils include metal foils (e.g., aluminum foil). The type of metal is not particularly limited, and may be a valve metal or an alloy containing a valve metal. The thickness of the cathode foil is not particularly limited, and may be in the range of 15 μm to 300 μm. The surface of the cathode foil may be roughened or subjected to chemical treatment as required.
[0090] The cathode foil may include a conductive coating. When the metal foil includes a valve metal, the coating may include carbon and at least one metal having a lower ionization tendency than the valve metal. Thus, the acid resistance of the metal foil is easily improved. When the metal foil includes aluminum, the coating may include at least one selected from carbon, nickel, titanium, tantalum and zirconium. Among them, the coating may include nickel and / or titanium from the perspective of cost and low resistance.
[0091] (Electrolyte layer)
[0092] As described above, the conductive polymer layer including the layer (PL), or the conductive polymer layer including the layer (PL) and the liquid component (L) can function as an electrolyte.
[0093] (Liquid component (L))
[0094] Examples of liquid components (L) include non-aqueous solvents and electrolytes. The electrolyte may include a non-aqueous electrolyte containing a non-aqueous solvent and a solute dissolved in the non-aqueous solvent. The liquid component (L) may contain a trace amount of water. It should be noted that in this specification, the liquid component (L) may be a component that is liquid at room temperature (25°C) or a component that is liquid at the temperature when the electrolytic capacitor is used.
[0095] The non-aqueous solvent may be an organic solvent or an ionic liquid. Examples of the non-aqueous solvent include polyols such as ethylene glycol and propylene glycol, cyclic sulfones such as sulfolane (SL), lactones such as γ-butyrolactone (γBL), amides such as N-methylacetamide, N,N-dimethylformamide, and N-methyl-2-pyrrolidone, esters such as methyl acetate, carbonate compounds such as propylene carbonate, ethers such as 1,4-dioxane, ketones such as methyl ethyl ketone, formaldehyde, and the like.
[0096] In addition, a polymer solvent can also be used as a non-aqueous solvent. Examples of polymer solvents include polyalkylene glycols, derivatives of polyalkylene glycols, compounds in which at least one hydroxyl group in a polyol is replaced with a polyalkylene glycol (including derivatives), etc. Specifically, examples of polymer solvents include polyethylene glycol (PEG), polyethylene glycol glycerol ether, polyethylene glycol diglycerol ether, polyethylene glycol sorbitol ether, polypropylene glycol, polypropylene glycol glycerol ether, polypropylene glycol diglycerol ether, polypropylene glycol sorbitol ether, polybutylene glycol, etc. Examples of polymer solvents further include copolymers of ethylene glycol-propylene glycol, copolymers of ethylene glycol-butylene glycol, copolymers of propylene glycol-butylene glycol, etc. The non-aqueous solvent can be used alone or in combination of two or more.
[0097] The liquid component (L) may contain an acid component and an alkaline component. Examples of the acid component include maleic acid, phthalic acid, benzoic acid, pyromellitic acid, and retsoric acid. Examples of the alkaline component include 1,8-diazabicyclo[5,4,0]undecene-7, 1,5-diazabicyclo[4,3,0]nonene-5, 1,2-dimethylimidazolinium, 1,2,4-trimethylimidazoline, 1-methyl-2-ethyl-imidazoline, 1,4-dimethyl-2-ethylimidazoline, 1-methyl-2-heptylimidazoline, 1-methyl-2-(3'heptyl)imidazoline, 1-methyl-2-dodecylimidazoline, 1,2-dimethyl-1,4,5,6-tetrahydropyrimidine, 1-methylimidazole, and 1-methylbenzimidazole.
[0098] The non-aqueous electrolyte solution includes a non-aqueous solvent and a solute (e.g., an organic salt) dissolved therein. Examples of the non-aqueous solvent constituting the non-aqueous electrolyte solution include the examples of the non-aqueous solvents described above. Examples of the solute include inorganic salts and organic salts. The so-called organic salt is a salt in which at least one of the anions and cations contains an organic substance. Examples of organic salts include trimethylamine maleate, triethylamine borodisalicylate, ethyldimethylamine phthalate, mono-1,2,3,4-tetramethylimidazolinium phthalate, mono-1,3-dimethyl-2-ethylimidazolinium phthalate, and the like.
[0099] In order to suppress dedoping of the dopant, the pH of the liquid component (L) may be set to less than 7.0 or less than 5.0, and may be set to 1.0 or more, or 2.0 or more. The pH may be set to 1.0 or more and less than 7.0 (eg, in the range of 2.0 to 5.0).
[0100] (other)
[0101] The electrolytic capacitor may include other components (leads, outer packaging, etc.) as necessary. The lead and outer packaging are not particularly limited, and known ones can be used.
[0102] (Electrolytic capacitors)
[0103] Hereinafter, the electrolytic capacitor of the present embodiment is sometimes referred to as an "electrolytic capacitor (E)". The electrolytic capacitor (E) can be manufactured using the manufacturing method (M) described above. Since the matters described for the manufacturing method (M) can also be applied to the electrolytic capacitor (E), repeated descriptions are sometimes omitted. In addition, the matters described for the electrolytic capacitor (E) can also be applied to the manufacturing method (M). It should be noted that the electrolytic capacitor (E) can also be manufactured using a manufacturing method other than the manufacturing method (M).
[0104] The electrolytic capacitor (E) includes a laminate of an anode foil and a cathode foil having a dielectric layer formed on the surface thereof, and a layer (layer (PL)) containing a conductive polymer and an insulating material (insulating material (I)) disposed between the dielectric layer formed on the surface of the anode foil and the cathode foil. As described above, the insulating material (I) is at least one selected from insulating fibers and insulating particles. No spacer is disposed between the anode foil and the cathode foil.
[0105] The electrolytic capacitor (E) does not include a separator disposed between the anode foil and the cathode foil, so the volume capacity density can be increased. On the other hand, the layer (PL) disposed between the anode foil and the cathode foil includes an insulating material (I), so the distance between the anode foil and the cathode foil can be set to a certain value or more.
[0106] The layer (PL) may further contain an additive (A) containing a hydroxyl group. The ratio Mh / Mt of the total formula weight Mh of the hydroxyl groups contained in the additive (A) to the molecular weight Mt of the additive may be within the above range.
[0107] Since examples of insulating fibers and insulating particles used for the insulating material (I) have been described above, repeated descriptions are omitted.
[0108] As described above, the laminate may be a laminate in which at least one anode foil and at least one cathode foil are laminated in one direction. Alternatively, the laminate may be a wound body of the anode foil and the cathode foil.
[0109] The layered product may be impregnated with a liquid component (L).
[0110] The ratio of the content of the conductive polymer in the layer (PL) to the content of the insulating substance (I) may be within the range exemplified for the ratio Ci / Cc of the content Ci to the content Cc in the dispersion (D1). The ratio of the content of the additive A in the layer (PL) to the content of the insulating substance (I) may be within the range exemplified for the ratio Ca / Ci of the content Ca to the content Ci in the dispersion (D1).
[0111] Hereinafter, an example of an electrolytic capacitor (E) is specifically described with reference to the accompanying drawings. The above-mentioned constituent elements can be applied to the constituent elements of the example described below. In addition, the constituent elements of the example described below can be changed based on the above-mentioned description. In addition, the matters described below can also be applied to the above-mentioned embodiment. In addition, in the example described below, constituent elements that are not necessary in the electrolytic capacitor of the present application can be omitted.
[0112] Figure 1 1 is a cross-sectional view schematically showing an electrolytic capacitor 100 according to an example of the present embodiment. Figure 2 1 is a schematic diagram showing a portion of capacitor element 10 included in electrolytic capacitor 100 . Electrolytic capacitor 100 is a laminated capacitor including a wound body (laminated body).
[0113] The electrolytic capacitor 100 includes a capacitor element 10, a bottomed case 101 accommodating the capacitor element 10, a sealing member 102 sealing an opening of the bottomed case 101, a seat plate 103 covering the sealing member 102, leads 104A and 104B extending from the sealing member 102 and penetrating the seat plate 103, and lead tabs 105A and 105B connecting the leads to electrodes of the capacitor element 10. The vicinity of the opening end of the bottomed case 101 is drawn inward, and the opening end is curled in a manner riveted to the sealing member 102.
[0114] The capacitor element 10 is, for example, Figure 2 The winding body is shown. The winding body is formed by winding the anode foil 11 and the cathode foil 12. A dielectric layer (not shown) is formed on the surface of the anode foil 11. The capacitor element 10 includes a conductive polymer layer (not shown) arranged between the anode foil 11 (more specifically, the dielectric layer on the surface of the anode foil 11) and the cathode foil 12. The conductive polymer layer includes a layer (PL) containing a conductive polymer and an insulating substance (I). The electrolytic capacitor 100 may also include a liquid component (L) (e.g., an electrolyte) impregnated in the capacitor element 10.
[0115] The outermost periphery of the winding body is fixed by the winding fixing tape 14. It should be noted that Figure 2 The diagram shows a partially unwound state before the outermost circumference of the wound body is fixed.
[0116] A partial cross section of an example of anode foil 11 having a conductive polymer layer formed thereon is schematically shown in FIG. Figure 3A In. Figure 3A As shown, dielectric layer 11a is formed on the surface of anode foil 11. Conductive polymer layer 21 is formed on dielectric layer 11a. Conductive polymer layer 21 is the above-mentioned layer (PL).
[0117] A partial cross section of another example of anode foil 11 having a conductive polymer layer formed thereon is schematically shown in FIG. Figure 3B In. Figure 3B As shown, a dielectric layer 11a is formed on the surface of the anode foil 11. A conductive polymer layer 21 (first conductive polymer layer) and a conductive polymer layer 22 (second conductive polymer layer) are formed on the dielectric layer 11a. The conductive polymer layer 21 is the above-mentioned layer (PL). The conductive polymer layer 22 is a conductive polymer layer that does not contain an insulating substance (I).
[0118] The electrolytic capacitor only needs to include at least one capacitor element, and may include a plurality of capacitor elements. The number of capacitor elements included in the electrolytic capacitor may be determined according to the intended use.
[0119] (appendix)
[0120] The following techniques are disclosed through the description of the above embodiments.
[0121] (Technique 1)
[0122] An electrolytic capacitor comprising:
[0123] A laminate of an anode foil and a cathode foil having a dielectric layer formed on the surface thereof, and
[0124] a layer containing a conductive polymer and an insulating material disposed between the dielectric layer and the cathode foil,
[0125] The insulating material is at least one selected from insulating fibers and insulating particles.
[0126] No separator is disposed between the anode foil and the cathode foil.
[0127] (Technique 2)
[0128] The electrolytic capacitor according to technology 1, wherein the layer further contains an additive containing a hydroxyl group,
[0129] The ratio Mh / Mt of the total formula weight Mh of the hydroxyl groups contained in the additive to the molecular weight Mt of the additive is 0.03 or more.
[0130] (Technique 3)
[0131] The electrolytic capacitor according to the first or second aspect, wherein the insulating fiber includes a fiber containing at least one substance selected from the group consisting of cellulose, rayon, polyester, polyimide, and nylon.
[0132] (Technique 4)
[0133] The electrolytic capacitor according to any one of techniques 1 to 3, wherein the insulating particles include particles containing at least one substance selected from the group consisting of polyolefin, polyester, polytetrafluoroethylene, and ceramic.
[0134] (Technique 5)
[0135] The electrolytic capacitor according to any one of techniques 1 to 4, wherein the laminate is a wound body of the anode foil and the cathode foil.
[0136] (Technique 6)
[0137] The electrolytic capacitor according to any one of techniques 1 to 5, wherein the laminate is impregnated with a liquid component.
[0138] (Technique 7)
[0139] A method for manufacturing an electrolytic capacitor includes an anode foil and a cathode foil having a dielectric layer formed on the surface thereof, and the manufacturing method sequentially comprises:
[0140] Step (i) of applying a dispersion containing a conductive polymer and an insulating substance to at least one element selected from the dielectric layer and the cathode foil and drying the dispersion, thereby forming a layer containing the conductive polymer and the insulating substance on the at least one element; and
[0141] step (ii) of laminating the anode foil and the cathode foil so that the layer is disposed between the dielectric layer and the cathode foil to form a laminated body,
[0142] The insulating material comprises at least one selected from insulating fibers and insulating particles.
[0143] In the step (ii), the anode foil and the cathode foil are stacked without a separator interposed therebetween.
[0144] (Technique 8)
[0145] According to the production method described in technology 7, the dispersion contains an additive containing a hydroxyl group and water as a dispersion medium,
[0146] The ratio Mh / Mt of the total formula weight Mh of the hydroxyl groups contained in the additive to the molecular weight Mt of the additive is 0.03 or more.
[0147] (Technique 9)
[0148] The production method according to claim 7 or 8, wherein the insulating fiber comprises at least one fiber selected from the group consisting of cellulose, rayon, polyester, polyimide and nylon.
[0149] (Technology 10)
[0150] The production method according to any one of techniques 7 to 9, wherein the insulating particles include at least one type of particles selected from the group consisting of polyolefin, polyester, polytetrafluoroethylene, and ceramic.
[0151] (Technology 11)
[0152] The manufacturing method according to any one of techniques 7 to 10, wherein in the step (ii), the anode foil and the cathode foil are stacked by winding the anode foil and the cathode foil.
[0153] (Technology 12)
[0154] The production method according to any one of techniques 7 to 11, further comprising, after the step (ii), a step (Z) of impregnating the laminate with a liquid component.
[0155] Example
[0156] Hereinafter, the present application will be described in more detail based on examples, but the present application is not limited to the examples.
[0157] (Experimental Example 1)
[0158] In Experimental Example 1, a plurality of electrolytic capacitors were produced and evaluated by the following method.
[0159] (Capacitor A1)
[0160] An electrolytic capacitor (capacitor A1) was produced by the following method.
[0161] (a) Preparation of components
[0162] An aluminum foil (thickness 100 μm) was etched to roughen the surface of the aluminum foil. The roughened surface of the aluminum foil was chemically treated to form a dielectric layer. In this way, an anode foil with dielectric layers formed on both sides was obtained. An aluminum foil (thickness 50 μm) was etched to roughen the surface of the aluminum foil to obtain a cathode foil.
[0163] (b) Preparation of dispersion (d1)
[0164] A dispersion (commercially available) was prepared by dispersing particles of poly(3,4-ethylenedioxythiophene) (PEDOT) doped with polystyrene sulfonic acid (PSS) in water. A mixed water of insulating fibers (insulating material (I)) formed of cellulose and an additive (A) were added to the dispersion to obtain a dispersion (d1). In the dispersion (d1), the content of the insulating fibers was set to 0.2% by mass, and the content of the additive (A) was set to 5.0% by mass. The content of PEDOT in the dispersion (d1) was set to 2.0% by mass. Ethylene glycol was used as the additive (A).
[0165] (c) Formation of conductive polymer layer
[0166] The dispersion (d1) was applied to one side of the anode foil (the surface of the dielectric layer) using a gravure coater. Thereafter, a drying process was performed to form a conductive polymer layer on one side of the anode foil (the surface of the dielectric layer). The drying process was performed by heating the anode foil coated with the dispersion (d1) at 125° C. for 5 minutes. Then, a conductive polymer layer was formed on the other side of the anode foil (the surface of the dielectric layer) using the same method.
[0167] The conductive polymer layer is formed on both surfaces of the cathode foil by the same method as that for forming the conductive polymer layer on both surfaces of the anode foil.
[0168] (d) Fabrication of capacitor elements
[0169] The anode foil and the cathode foil are cut into a predetermined size. The anode lead connector and the cathode lead connector are connected to the anode foil and the cathode foil. Then, the anode foil and the cathode foil are wound without a spacer. The anode lead and the cathode lead are connected to the ends of each lead connector protruding from the wound body. The resulting wound body is subjected to a chemical treatment again to form a dielectric layer on the end face of the anode foil. The end of the outer surface of the wound body is fixed with a winding fixing tape to obtain a capacitor element.
[0170] (e) Infiltration of liquid components
[0171] Phthalic acid and triethylamine (alkali component) were dissolved in ethylene glycol (solvent) at a total concentration of 25 mass % to prepare an electrolyte solution (liquid component (L)). The capacitor element was immersed in the electrolyte solution for 5 minutes in a reduced pressure atmosphere (40 kPa). Thus, the capacitor element (laminated body) was impregnated with the electrolyte solution.
[0172] (f) Sealing of capacitor elements
[0173] The capacitor element impregnated with electrolyte is sealed to produce Figure 1 The electrolytic capacitor shown in the figure was then aged at 95°C for 90 minutes while applying a voltage. Thus, an electrolytic capacitor (capacitor A1) was obtained.
[0174] (Fabrication of capacitor C1)
[0175] An electrolytic capacitor (capacitor C1) was produced by the following method.
[0176] (a) Preparation of dispersion (CD1)
[0177] Dispersion (cd1) was prepared by the same method and conditions as those of dispersion (d1) except that no insulating fiber was added. Dispersion (cd1) was a dispersion obtained by dispersing particles of poly(3,4-ethylenedioxythiophene) (PEDOT) doped with polystyrene sulfonic acid in water.
[0178] A capacitor C1 was produced using the dispersion (cd1) in the same manner as the capacitor A1 except that the dispersion used for forming the conductive polymer layer on each component member was changed as shown in Table 1.
[0179] (evaluate)
[0180] The withstand voltage and the equivalent series resistance (ESR) at 100 kHz of the produced capacitors were measured. Note that the evaluation was performed by preparing three capacitors for each of the capacitors A1 and C1 and calculating the arithmetic average of the measured values.
[0181] Some of the formation conditions of the conductive polymer layer and the evaluation results are shown in Table 1. Note that capacitor A1 is a capacitor (E) of the present embodiment, and capacitor C1 is a capacitor of a comparative example. The withstand voltage and ESR in Table 1 are the arithmetic mean values of the measured values of three capacitors.
[0182] [Table 1]
[0183]
[0184] As shown in Table 1, by using the dispersion (d1) to which insulating fibers are added, the withstand voltage can be maintained even without using a spacer. In addition, the ESR of the capacitor A1 is almost the same as the ESR of the comparative example C1. As described above, according to this embodiment, a highly reliable electrolytic capacitor can be manufactured even without a spacer.
[0185] Industrial Applicability
[0186] The present application can be applied to electrolytic capacitors and methods for manufacturing the same.
[0187] Although the present invention has been described with respect to the present preferred embodiments, such disclosure should not be interpreted in a limiting sense. Upon reading the above disclosure, various modifications and changes will undoubtedly be apparent to those skilled in the art in the technical field of the present invention. Therefore, the scope of the appended claims should be interpreted as including all modifications and changes without departing from the true spirit and scope of the present invention.
[0188] Description of Reference Numerals
[0189] 10: capacitor element, 11: anode foil, 12: cathode foil, 14: winding fixing tape, 100: electrolytic capacitor, 101: bottom case, 102: sealing member, 103: seat plate.
Claims
1. An electrolytic capacitor, comprising: A laminate of an anode foil and a cathode foil having a dielectric layer formed on the surface thereof, and a layer containing a conductive polymer and an insulating material disposed between the dielectric layer and the cathode foil, The insulating material is at least one selected from insulating fibers and insulating particles. No separator is disposed between the anode foil and the cathode foil.
2. The electrolytic capacitor according to claim 1, wherein: The layer further comprises an additive containing a hydroxyl group, The ratio Mh / Mt of the total formula weight Mh of the hydroxyl groups contained in the additive to the molecular weight Mt of the additive is 0.03 or more.
3. The electrolytic capacitor according to claim 1 or 2, wherein: The insulating fiber includes a fiber containing at least one substance selected from the group consisting of cellulose, rayon, polyester, polyimide, and nylon.
4. The electrolytic capacitor according to claim 1 or 2, wherein: The insulating particles include particles containing at least one substance selected from the group consisting of polyolefin, polyester, polytetrafluoroethylene, and ceramics.
5. The electrolytic capacitor according to claim 1 or 2, wherein: The laminated body is a wound body of the anode foil and the cathode foil.
6. The electrolytic capacitor according to claim 1 or 2, wherein: The laminated body is impregnated with a liquid component.
7. A method for manufacturing an electrolytic capacitor, comprising an anode foil and a cathode foil having a dielectric layer formed on the surface thereof, the method comprising: Step (i) of applying a dispersion containing a conductive polymer and an insulating substance to at least one element selected from the dielectric layer and the cathode foil and drying the dispersion, thereby forming a layer containing the conductive polymer and the insulating substance on the at least one element; and step (ii) of laminating the anode foil and the cathode foil so that the layer is disposed between the dielectric layer and the cathode foil to form a laminated body, The insulating material includes at least one selected from insulating fibers and insulating particles. In the step (ii), the anode foil and the cathode foil are stacked without a separator interposed therebetween.
8. The manufacturing method according to claim 7, wherein: The dispersion comprises an additive containing a hydroxyl group and water as a dispersion medium, The ratio Mh / Mt of the total formula weight Mh of the hydroxyl groups contained in the additive to the molecular weight Mt of the additive is 0.03 or more.
9. The manufacturing method according to claim 7 or 8, wherein: The insulating fiber includes at least one fiber selected from the group consisting of cellulose, rayon, polyester, polyimide, and nylon.
10. The manufacturing method according to claim 7 or 8, wherein: The insulating particles include at least one type of particles selected from the group consisting of polyolefin, polyester, polytetrafluoroethylene, and ceramic.
11. The manufacturing method according to claim 7 or 8, wherein: In the step (ii), the anode foil and the cathode foil are stacked by winding the anode foil and the cathode foil.
12. The manufacturing method according to claim 7 or 8, wherein: After the step (ii), the method further includes the step (Z) of impregnating the laminate with a liquid component.
Citation Information
Patent Citations
JP1975062738A
Electrolytic capacitor having polymer outer layer, and its manufacturing method
JP2007027767A